Direct Medical Cost for Acute Ischemic Stroke Patients in Vietnam - Nguyen, Tuan Van; Hoang, Minh Van; Doan, Huyen Thi; Nguyen, Van Minh (Journal of Population and Social Studies [JPSS], 2024)
Ischemic stroke is one of the leading causes of global disease burden. Vietnam, among other low- and middle-income countries, bears nearly 90% of the ischemic stroke burden. This study was a cost-of-illness study conducted from the healthcare system perspective to estimate the direct medical costs and associated factors for acute ischemic stroke patients at Bach Mai Hospital, a major hospital in Hanoi, Vietnam. A total of 500 eligible patients with acute ischemic stroke at the Neurology Department of Bach Mai Hospital from July 2021 to December 2021 were included. Patient characteristics and treatment information were collected via medical records and patient interviews. The majority of the patients were men (65.8%), with a mean age of 65.3 years. The average direct medical cost per patient was 10.5 ± 7.3 million Vietnam Dong ( 454.2 ± 313.8 US dollars. Factors significantly associated with higher direct medical costs were the duration of stay, stroke severity, complications, number of comorbidities, and intravenous thrombolysis treatment. The study highlighted the need for a reduction in the duration of hospital stay and an improvement in onset-to-hospital arrival time.